(3EMdGd VQjHI GdeHjYGJ hGdJLGQI GdNGQLjI (B:s (3GdCKQ aj Xd GJaGbGJ GdJLGQI GdYGdejI (B/s - (3YHO GdZfj, jMjis ((3GdGScfOQjI(B: s (3eQcR OdJG ddWHGYI(B, s, 1998)
(3eaghe GdVQjHI Ydi GdbjeI GdeVGaI heVehfgG, edGeM GdVQjHI GdYGeI Ydi GdeHjYGJ hJWhQgG aj eUQ NdGd GdJSYjfjGJ, GdBKGQ GdeMJedI dGMdGd VQjHI GdbjeI GdeVGaI Ydi hVY GdJLGQI GdOhdjIs
(3GdeQGLY U(B.97 (3GdedGMb U(B.91s
Keywords: (3GdJLGQI GdOhdjIs; (3GdVQGFHs